2016
DOI: 10.1111/gcb.13510
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone

Abstract: Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal (EM) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
121
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 81 publications
(138 reference statements)
11
121
1
Order By: Relevance
“…In contrast, the opposite response (i.e. decreased plant photosynthesis along with decreased EMF relative abundance and richness under warming) has been recently reported in a boreal/temperate ecotone ecosystem located near the lower latitudinal limit of the host plant range where productivity is limited by water availability (Fernandez et al., ). We found that warming, rainfall reduction and their combination altered ectomycorrhizal community structure and led to drastic decreases in the relative abundance of EMF sequences in the rhizosphere of H. squamatum , which is the only EMF host plant species at our study site.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the opposite response (i.e. decreased plant photosynthesis along with decreased EMF relative abundance and richness under warming) has been recently reported in a boreal/temperate ecotone ecosystem located near the lower latitudinal limit of the host plant range where productivity is limited by water availability (Fernandez et al., ). We found that warming, rainfall reduction and their combination altered ectomycorrhizal community structure and led to drastic decreases in the relative abundance of EMF sequences in the rhizosphere of H. squamatum , which is the only EMF host plant species at our study site.…”
Section: Discussionmentioning
confidence: 95%
“…saprotrophs) did not change significantly in the climate manipulation treatments. This strongly suggests that altered EMF community structure and decreased relative abundance of EMF sequences with climate manipulation was linked to plant responses and largely driven by decreased carbon supply to mycorrhizae from their stressed host plants under hotter and/or drier conditions (Castaño et al., ; Fernandez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative values were considered zeros before data were finally converted to relative abundances (as percentage of normalized read numbers) as per Fernandez et al . (). The negative binomial model performed within D e S eq 2 can simultaneously account for variation in library sizes and biological variability better than simply subsampling to a uniform sequencing depth alone.…”
Section: Methodsmentioning
confidence: 97%
“…The relative abundance of ECMF exploration strategies (% of ECMF OTUs) per site were assigned by matching ECMF genera against published lists (Agerer, ; Tedersoo & Smith, ), which are available online (http://www.deemy.de). Strategies were assigned to the following categories according to Fernandez et al (): contact short (CS), contact medium (CM) and medium long (ML). Because of potential differences in the relationship between DNA copy number and fungal biomass, particularly among functional groups known to differ in their morphology, we restricted our analyses to intraguild comparisons (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Climate change can alter the community composition of ECMF by pushing fungi (Kipfer, Egli, Ghazoul, Moser, & Wohlgemuth, ) or their host plants (Fernandez et al, ) outside their ranges of physiological tolerance (Pickles, Egger, Massicotte, & Green, ). However, most studies to date that have examined ECMF or whole fungal community responses to simulated climate change have found fairly small effects (Fernandez et al, ; Mucha et al, ; Parrent, Morris, & Vilgalys, ; Tu et al, ) relative to natural changes in fungal communities observed along large natural gradients of temperature and precipitation (Jarvis, Woodward, Alexander, & Taylor, ; Nottingham et al, ; Peay et al, ; Talbot et al, ; Tedersoo et al, ). Yet, few datasets currently exist with spatial resolution necessary to make accurate predictions of ECMF response to climate change across relevant geographic regions (Mohan et al, ).…”
Section: Introductionmentioning
confidence: 99%